Ostracod valve counts at IODP Site 347-M0059 (Baltic Sea), upper 52.3 meters composite depth - Stepanova, Anna Yu (PANGAEA, 2017)
A total of 75 30CC sediment samples were processed for ostracod analysis. Ostracods were picked from the entire sample residues and their valves identified and counted. At site M0059 two ecological classes of ostracods in relation to salinity were distinguished based on ecological data and distribution of modern taxa in the Baltic Sea and adjacent areas: freshwater and brackish-marine. Among brackish-marine ostracods very shallow and deeper water species were distinguished based on ecological data.